Epilepsy - Cervenka, Mackenzie C.; Kaplan, Peter W. (Seminars in Neurology, 2016)
The accurate diagnosis and classification of seizures is critical in informing prognosis and determining appropriate antiseizure treatments for patients with epilepsy. The electroencephalogram is the gold standard for diagnosis. Obtaining a thorough history, performing a careful physical examination, and selecting appropriate diagnostic studies are also essential in determining the underlying seizure etiology. The authors provide clinical pearls and pitfalls in the diagnosis and management of epilepsy.
Keywords: seizure; epilepsy; convulsion; antiseizure drug; electroencephalogram